The social-sensory interface: category interactions in person perception - Freeman, Jonathan; Johnson, Kerri; Adams, Reginald; Ambady, Nalini (Frontiers in Integrative Neuroscience, 2012)
Research is increasingly challenging the claim that distinct sources of social information—such as sex, race, and emotion—are processed in discrete fashion. Instead, there appear to be functionally relevant interactions that occur. In the present article, we describe research examining how cues conveyed by the human face, voice, and body interact to form the unified representations that guide our perceptions of and responses to other people. We explain how these information sources are often thrown into interaction through bottom-up forces (e.g., phenotypic cues) as well as top-down forces (e.g., stereotypes and prior knowledge). Such interactions point to a person perception process that is driven by an intimate interface between bottom-up perceptual and top-down social processes. Incorporating data from neuroimaging, event-related potentials (ERP), computational modeling, computer mouse-tracking, and other behavioral measures, we discuss the structure of this interface, and we consider its implications and adaptive purposes. We argue that an increased understanding of person perception will likely require a synthesis of insights and techniques, from social psychology to the cognitive, neural, and vision sciences.